Schematic Mediation in the Critique of Pure Reason: Synthesis of Imagination and Schematism - Ferreira Oliveira, Eliakim (Con-Textos Kantianos. International Journal of Philosophy, 2026)
My aim in this article is to propose an interpretation of the schematism of the pure concepts of the understanding, in order to elucidate the relation between schematism and the a priori synthesis of imagination. The guiding questions may be formulated as follows: What exactly does Kant mean when he claims that the “schema is a product of the imagination”? What is the relation between this statement and the one in §10, according to which synthesis is an effect of imagination, or the one in the B Deduction, according to which imagination performs a transcendental synthesis? I defend the thesis that, insofar as imagination determines time a priori according to the unity of the categories, it translates each of them into a temporal language (or a language of transcendental imagination), that is, it gives sense to the category in the determination of the object when it is thought according to temporal patterns.